THE INTERSECTION OF TECHNOLOGY AND JUSTICE: MODERN INVESTIGATIVE TECHNIQUES - Singh, Janmejay; Mishra, Taru; Jaiswal, Ayushi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Let’s start with understanding the meaning of the above quotation which is, that to provide justice properly to the needy person few things should always be kept in mind the legal system (lawyers, justice, law officers) should always check the possible ways to provide justice to the needy person, no one should be kept away from the justice. For that, many lawyers should provide free legal aid to needy people who cannot afford the court and lawyer’s fees. Now let us understand the basic meaning of the terms of the topic one by one. Let's start with the term investigation, it is a type of examination done to find some facts about the situation which may help further to provide justice because a single fact related to the case and even change the whole decision of the case can be done by some officially or unofficially by one who has the permission for it. Now, Justice means fair behavior with other people means they should be treated equally and no discrimination should be done on any basis, people around the world when they are struck in a case situation demand justice for them when they are innocent then the legal system must provide justice properly to the needy person. Earlier there were different methods to investigate the case which we will discuss later but after the technological advancement, there was a drastic change in the methods or strategies used by the officers to investigate the case, with the change in technology the methods to collect pieces of evidence, finding out DNA prints has become a lot easier for the officer doing the investigation.